Influência da transferência de ovos para o nascedouro em diferentes momentos de incubação no rendimento de incubação e qualidade de pintos - Petrocelli, Adriana Tereza Machado de Moura (2013)
This paper aimed at determining the best moment to transfer hatching eggs to the hatcher, optimizing the incubation period, increasing the incubation yield with no interference at chicks quality when compared to the traditional incubation method. The experiment was carried out at a hatchery in the city of Uberlândia, State of Minas Gerais, using broiler breeders from the commercial line Cobb. The experimental design was 2X4, considering two breeders age (35 weeks and 52 weeks old) and four moments of transference from incubator to the hatcher, which were at 16, 17, 18 and 19 days of incubation. After the transference, the eggs remained in the hatcher during five, four, three and two days, respectively, totaling about 504 hours of incubation. Each treatment included the evaluation of 90 hatched chicks, being 30 chicks evaluated in three heights of the incubation cart (first, middle and last tray). The parameters evaluated were: chick length and weight, yolk, heart, liver and intestine weight. There was influence of the breeders age related to the parameters analyzed, where it could be observed at chicks from older hens largest egg weight, chick length and weight, yolk, heart and liver weight but only intestine showed no difference among the breeders ages. There was no influence of the transference moment on body mass of chicks at birth, but there was an increase in length of chicks closer the transferring age at 19 days. There was influence of the transference moment on the organs of chicks transferred to the hatcher after 16 days of incubation, where it was observed the trend of further organs development compared to other times of transference, showing that in order to acquire the body mass obtained there was a greater physiological demand of organs in these birds. As a suggestion, further papers can be performed to analyze the performance data at the field.